The Tourism Potential of Sukasantai Farmstay in Sukamaju Village, Sukabumi Regency, West Java - Friska Angelina; Sharleen Sharleen; Gary Leonis Geoffrey (Jurnal Studi Perhotelan dan Pariwisata, 2025)
Purpose: This study documents and analyzes the tourism potential of Sukasantai Farmstay, an agritourism enterprise located at the foot of Mount Gede in Sukamaju Village, Sukabumi Regency, West Java, that combines accommodation, organic farming, livestock management, and nature-based recreation within a sustainability-oriented farm-to-table model. The research assesses the destination across five dimensions of the tourism attraction development framework and examines its impact on the surrounding community.Methodology: A qualitative case study design was used, combining in-depth interviews with the co-owner, garden manager, kitchen staff, and four visiting guests, together with two days of direct field observation and secondary document review. Results: Sukasantai demonstrates strong potential across all five criteria, supported by diverse natural attractions, a broad activity portfolio, quality accommodation with digital detox features, authentic farm-produced goods, and multi-modal transportation access. Community impact is evidenced through fair local employment and pandemic-resilient farm sales.Conclusions: Sukasantai constitutes a well-developed agritourism destination with meaningful community and educational value.Limitations: The study relies on a single field visit and a small informant sample.Contributions: This research offers the first systematic academic documentation of Sukasantai using an established tourism attraction framework, contributing empirical insight into organic farming-based hospitality models in rural West Java.